Measures to Predict The Individual Variability of Corticospinal Responses Following Transcranial Direct Current Stimulation - Nuzum, Nathan D.; Hendy, Ashlee M.; Russell, Aaron P.; Teo, Wei-Peng (Frontiers in Human Neuroscience, 2016)
Individual responses to transcranial direct current stimulation are varied and therefore potentially limit its application. There is evidence that this variability is related to the contributions of I-waves recruited in the cortex. The latency of MEPs can be measured through transcranial magnetic stimulation, allowing an individual’s responsiveness to tDCS to be determined. However, this method, the single-pulse method, requires several different orientations of the TMS coil, potentially affecting its reliability. Instead, we propose a paired-pulse TMS paradigm targeting I-waves as an alternative method. This method uses one orientation that reduces inter- and intra-trial variability. It was hypothesised that the paired-pulse method would correlate more highly to tDCS responses than the single-pulse method. In a randomised, double blinded, cross-over design, 30 healthy participants completed two sessions, receiving 20mins of either anodal (2mA) or sham tDCS. TMS was used to quantify SICF at ISIs of 1.5, 3.5 and 4.5ms. Latency was determined in the posterior-anterior (PA), anterior-posterior (AP) and latero-medial coil orientations (LM). The relationship between latency, SICF measures, and the change in suprathreshold MEP amplitude size following tDCS were determined with Pearson’s correlations. TMS measures, SICI and SICF were also used to determine responses to a-tDCS. Neither of the latency differences nor the SICF measures correlated to the change in MEP amplitude from pre-post tDCS (all P > 0.05). Overall, there was no significant response to tDCS in this cohort. This study highlights the need for testing the effects of various tDCS protocols on the different I-waves. Further research into SICF and whether it is a viable measure of I-wave facilitation is warranted.